2001
DOI: 10.1159/000045884
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Long-Term Diabetes on Renal Glycogen Metabolism in the Rat

Abstract: Background/Aims: The effects of acute insulin deficiency on the kidney have been investigated in animal models of experimental diabetes; however, the impact of long-term diabetes has not been determined. Methods: We measured renal glycogen contents in streptozotocin (STZ)-diabetic rats 3 weeks (n = 12) or 9 months (n = 12) after the induction of diabetes, and in 2 groups of control rats of similar age (n = 16 and n = 12, respectively), in the fed state and after a 24-hour fast. Results: Diabetic rats had high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…The glycogen nephrosis, characteristic of diabetic nephropathy, has been extensively investigated (Holck and Rasch, 1993;Meyer et al, 1998;Nannipieri et al, 2001;Rasch, 1984Rasch, , 1991. Rasch and Holck (Holck and Rasch, 1993;Rasch, 1984Rasch, , 1991 reported that the lesion is confined to the distal tubules, including the thick ascending limbs (TALs) in the cortex and the outer stripe of the outer medulla (OSOM).…”
mentioning
confidence: 99%
“…The glycogen nephrosis, characteristic of diabetic nephropathy, has been extensively investigated (Holck and Rasch, 1993;Meyer et al, 1998;Nannipieri et al, 2001;Rasch, 1984Rasch, , 1991. Rasch and Holck (Holck and Rasch, 1993;Rasch, 1984Rasch, , 1991 reported that the lesion is confined to the distal tubules, including the thick ascending limbs (TALs) in the cortex and the outer stripe of the outer medulla (OSOM).…”
mentioning
confidence: 99%
“…A key morphological change associated with sustained hyperglycaemia in the diabetic kidney is the accumulation of glycogen [1], known as Armanni-Ebstein lesions [2]. Glycogen accumulation predominantly occurs in the cortical and outer medullary region of the diabetic kidney, primarily localised in the thick ascending limb of the loop of Henle and distal tubules [1].…”
Section: Introductionmentioning
confidence: 99%
“…Glycogen accumulation predominantly occurs in the cortical and outer medullary region of the diabetic kidney, primarily localised in the thick ascending limb of the loop of Henle and distal tubules [1]. The accumulation of glycogen in these cells has been suggested by several studies to compromise their viability and thus contribute to renal impairment in diabetic individuals [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have described the characteristics of glycogen nephrosis [4, 5, 7, 23, 24]. However, none has addressed the possible alterations in cell-to-matrix interactions for these glycogen-accumulating clear cells.…”
Section: Introductionmentioning
confidence: 99%